Effect of the changed electrolytic cell on the current efficiency in FFC Cambridge process - Hu, Meilong; Zhengfeng, Qu; Chenguang, Bai; Hu, Di; Chen, George Z. (Nihon Kinzoku Gakkai, 2017)
Low current efficiency of the FFC Cambridge process made it no obvious advantages in cost compared with the traditional process to produce metals. Effect of the changed electrolysis cell on the current efficiency has been studied. Put the cathode into an alumina tube with a hole can efficiently avoid short circuit and the cathode contaminated by carbon produced from graphite anode. The results show that the current efficiency can be improved greatly by reducing the electric field intensity in the electrolysis cell. The high background current is mainly caused by the electronic conductivity in the electrolysis cell. Otherwise, pollution of the cathode is avoided, the depletion of the anode sharply decreases and the deoxidation of the samples greatly improve when using the improvement electrolysis cell.